Nocturnal blood pressure surge in seconds is associated with arterial stiffness independently of conventional nocturnal blood pressure variability in suspected obstructive sleep apnea patients - Ayako Kokubo; Mitsuo Kuwabara; Naoko Tomitani; Shingo Yamashita; Toshikazu Shiga; Kazuomi Kario (The Journal of Clinical Hypertension, 2023)
Abstract Nocturnal blood pressure (BP) surge in seconds (sec‐surge), which is characterized as acute transient BP elevation over several tens of seconds is induced by obstructive sleep apnea (OSA) and OSA‐related sympathetic hyperactivity. The authors assessed the relationship between sec‐surge and arterial stiffness in 34 nocturnal hypertensive patients with suspected OSA (mean age 63.9 ± 12.6 years, 32.4% female). During the night, they had beat‐by‐beat (BbB) BP and cuff‐oscillometric BP measurements, and brachial‐ankle pulse wave velocity (baPWV) was assessed as an arterial stiffness index. Multiple linear regression analysis revealed that the upward duration (UD) of sec‐surge was significantly associated with baPWV independently of nocturnal oscillometric systolic BP variability (β = .365, p = .046). This study suggests that the UD of sec‐surge, which can only be measured using a BbB BP monitoring device, may be worth monitoring in addition to nocturnal BP level.